Kritik terhadap Relasi Antagonistis Timur-Barat - Mukhammad Zamzami (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
The seeds of the clash of thought between the East and the West have become a pin point on the valuable literature of the classical west to take a part on such issues. In short, Hegel’s claim on the philosophical history, Darwinism on the evolutional theory and Marxism on the capitalism join in this complex debate. Those three figures play a role in formulating the existence of west civilization with its hegemonic characteristic. The prosperous study on looking another civilization in black-white discourse takes part in growing animosity among civilization. Civilization is a total number of material achievements and thoughts from many generations. Civilization cannot appear from few people for it is a spontaneous design of human being. This article attempts to explore two leading civilizations in the world, Islam and the West. When Islam, which is identical with the East, has tried to observe the West by using Occidentalism as its epistemological approach, polemic and debate become apparent. The tension between the West and the East takes another new volume. This article attempts to elucidate the antagonistic-relationship between the East and the West, the Occidentalism, and epistemological efforts to build the dialogue of civilization.